Undernutrition among adults in India: the significance of individual-level and contextual factors impacting on the likelihood of underweight across sub-populations. Issue 1 (12th August 2016) - Siddiqui, Md Zakaria; Donato, Ronald
Abstract: Objective: To investigate the extent to which individual-level as well as macro-level contextual factors influence the likelihood of underweight across adult sub-populations in India. Design: Population-based cross-sectional survey included in India's National Health Family Survey conducted in 2005–06. We disaggregated into eight sub-populations. Setting: Multistage nationally representative household survey covering 99 % of India's population. Subjects: The survey covered 124 385 females aged 15–49 years and 74 369 males aged 15–54 years. Results: A social gradient in underweight exists in India. Even after allowing for wealth status, differences in the predicted probability of underweight persisted based upon rurality, age/maturity and gender. We found individual-level education lowered the likelihood of underweight for males, but no statistical association for females. Paradoxically, rural young (15–24 years) females from more educated villages had a higher likelihood of underweight relative to those in less educated villages; but for rural mature (>24 years) females the opposite was the case. Christians had a significantly lower likelihood of underweight relative to other socio-religious groups (OR=0·53–0·80). Higher state-level inequality increased the likelihood of underweight across most population groups, while neighbourhood inequality exhibited a similar relationship for the rural young population subgroups only. Individual states/neighbourhoods accounted for 5–9 % of the variation in the prediction of underweight. We found that rural young females represent a particularly highly vulnerable sub-population. Conclusions: Economic growth alone is unlikely to reduce the burden of malnutrition in India; accordingly, policy makers need to address the broader social determinants that contribute to higher underweight prevalence in specific demographic subgroups.